Neuroimaging in Neonatal Encephalopathy - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at St Francis Medical Center, Cape Girardeau, MO, and multiple centers in the US, using a database from the Vermont Oxford Network Registry, studied the pattern of use and findings of computed tomography, MRI, and intracranial ultrasound in the evaluation of infants with neonatal encephalopathy.